Impact of Sociodemographic Factors on Quality of Life of Health care Workers - Iqbal, Dr. Muhammad Shahid (Asian Journal of Pharmaceutics (AJP), 2021)
Purpose: Several studies have proved that poor health state is a major risk factor for numerous unwanted effects. This study aimed to assess quality of life (QoL) and determine various factors persuading QoL in health care workers (HCWs). Materials and Methods: A cross-sectional study using WHOQOL-BREF research tool was designed and conducted among HCWs in Al-Kharj, Saudi Arabia. Descriptive, comparative, and inferential statistics were performed using Statistical Package for the Social Sciences (SPSS). Results: A total of 289 HCWs participated in the final study, 48% were male and 52% were female. A total of 69% of the study HCWs were married, and 58% had <10 years of experience. Statistically significant differences (P < 0.05) in marital status, education level, income, and year of practice were found in various domains of WHOQOL-BREF. Overall, mixed findings in various domains of WHOQOL-BREF were observed regarding HCWs’ QoL in the studied cohort. Conclusion: The results indicated that HCWs had good-excellent QoL in various domains of WHOQOL-BREF in Saudi Arabia